2004
DOI: 10.1007/s00198-004-1690-6
|View full text |Cite
|
Sign up to set email alerts
|

A new significant and independent risk factor for falls in elderly men and women: a low creatinine clearance of less than 65�ml/min

Abstract: Objectives: Because impaired renal function is detrimental for the conversion of calcidiol to calcitriol (D-hormone) and since D-hormone analogues have been shown to decrease the risk of falls, we investigated whether creatinine clearance (CrCl) is associated with the number of fallers and falls in elderly men and women. Methods: Within a randomized controlled study, we observed for 36 weeks 186 placebo-treated community-dwelling elderly men and women over 70, in an attempt to determine the influence of baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 47 publications
(67 reference statements)
3
41
0
2
Order By: Relevance
“…Recent studies have reported that poor renal function is a risk factor for falls in older adults (23). We found a linear association between fall risk and cysC, suggesting that even modest declines in renal function are a risk factor for falls.…”
Section: Falls In Older Diabetic Adultssupporting
confidence: 65%
“…Recent studies have reported that poor renal function is a risk factor for falls in older adults (23). We found a linear association between fall risk and cysC, suggesting that even modest declines in renal function are a risk factor for falls.…”
Section: Falls In Older Diabetic Adultssupporting
confidence: 65%
“…Although a study by Boudville et al 20 , and this study did not find association between PTH levels and falling, some researchers observed that higher PTH levels are related to the latter 27,28 , considering that bone fragility, muscle weakness, and poor postural balance are independent risk factors for the occurrence of falls and fractures 29 . Therefore, high PTH levels associated with low vitamin D levels in individuals on hemodialysis cause a negative impact on muscle strength and functional mobility, because they cause the atrophy of muscle fibers of rapid concentration, thus predisposing the individuals to falling 11 . The fact that no association was found suggests the necessity of studies that investigate this occurrence.…”
Section: Risk Of Falling and The Parathyroid Hormonementioning
confidence: 99%
“…Studies report the association among creatinine clearance, a decrease in the serum levels of calcitriol, and vitamin D receptors in the muscle with an increase in the risk of falling [7][8][9] . The low levels of calcitriol associated with high levels of PTH are related to myopathy, loss of balance, the occurrence and medical history of falls [10][11][12] , and due to the latter, the decline of physical functioning 13 . Therefore, recognizing the importance of evaluating the fear of falling in patients with CKD, this study aimed at assessing the capacity of the FES-I, the serum levels of PTH, and the length of time on hemodialysis treatment (LTH) in discerning falling from non-falling patients with CKD under hemodialysis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…in age-matched populations (15)(16)(17) and have an overall lower level of independent functioning (18 -20) and increased burden of cognitive impairment (21)(22)(23). Fall incidence rates have been estimated between 1.2 to 1.6 falls per person-year for dialysis patients whoa re older than 65 yr (16,23).…”
Section: Frailtymentioning
confidence: 99%